Epidemiological Situation on Anthrax in 2018, the Forecast for 2019 - A. G. Ryazanova; E. B. Ezhlova; N. D. Pakskina; O. V. Semenova; L. Yu. Aksenova; E. I. Eremenko; N. P. Buravtseva; T. M. Golovinskaya; N. G. Varfolomeeva; D. K. Chmerenko; G. A. Pechkovsky; A. N. Kulichenko (Проблемы особо опасных инфекций, 2019)
Analysis of the anthrax incidence in the Russian Federation over the period of 2009–2018 showed that the infections among the population were recorded in 14 regions of 6 Federal Districts. 23 anthrax outbreaks among people were revealed, where 90 people got sick with 3 lethal outcomes. In comparison to the previous ten-year period (1999–2008), the number of cases of the disease was reduced by 1.6 times. Three cases of cutaneous anthrax were registered in two constituent entities of the Russian Federation in 2018 – the Republic of Dagestan (1) and the Republic of Tyva (2). Outbreaks of infection among livestock animals and people were recorded in such neighboring states as Georgia, Kazakhstan, China, Kyrgyzstan, and Ukraine. Epizootiological and epidemiological instability as regards anthrax was observed in several countries of Asia and Africa. Human infection occurred as a result of contact with sick and dead animals in the process of slaughter and cutting of carcasses, consuming infected meat. Anthrax morbidity rates among animals and people in the Russian Federation in 2019 will depend on the comprehensiveness of implementation of the plans for anthrax prevention, and in case those plans will be realized at the maximum scale incidence will be limited to single cases.